2007
DOI: 10.1007/s11747-007-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of new technologies: organizational adaptation to business environments

Abstract: The practice of introducing new technologies into the corporate environment has become a well-accepted principle for sustaining or advancing competitive advantages. The current study focuses on the environmental and managerial factors associated with the successful utilization of new technologies. To this end, the suggested framework examines the efforts put forth by the two parties involved (the firm buying and the firm supplying the new technology). We use 112 matched data collected from the suppliers and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 64 publications
(77 reference statements)
1
49
0
Order By: Relevance
“…A cultural mandate and a clear vision for managing the transfer of knowledge across the firm are requisites for enhancing customer data (Jayachandran et al 2005;Kim and Pae 2007;Verhoef et al 2010). Consistent with this view, DeshpandĂ© and Webster (1989, p. 4) define organizational culture as "the pattern of shared values and beliefs that help individuals understand organizational functioning and thus provide them norms for behavior in the organization."…”
Section: Antecedents Of Data Quality: Organizational Learning Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…A cultural mandate and a clear vision for managing the transfer of knowledge across the firm are requisites for enhancing customer data (Jayachandran et al 2005;Kim and Pae 2007;Verhoef et al 2010). Consistent with this view, DeshpandĂ© and Webster (1989, p. 4) define organizational culture as "the pattern of shared values and beliefs that help individuals understand organizational functioning and thus provide them norms for behavior in the organization."…”
Section: Antecedents Of Data Quality: Organizational Learning Processesmentioning
confidence: 99%
“…The failure of CRM systems has been attributed to the inability to facilitate and enhance the organization-wide transfer of customer information (Jayachandran et al 2005;Kim and Pae 2007;Verhoef et al 2010). For example, Homburg, Grozdanovic, and Klarmann 2007 found that changing the affective organizational system (i.e., customer culture) vis-Ă -vis CRM practices had a greater impact on performance than improving cognitive organizational systems (i.e., information technology).…”
Section: Organizational Learning Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…E-service innovation creates value by enabling service providers to use electronic technologies to improve customer-firm interactions and reduce service production risk (Hinnant & O'Looney, 2003;. Valuable outside information can be integrated with other customer records to improve the efficiency and effectiveness of service delivery (Kim & Jae, 2007). Xu, Sharma, and Hackney (2005) indicated that web-service innovation can be examined by "identify its unique characteristics which make it distinct to all other innovations" (p. 322); specifically, web-service innovations are aimed at achieving the following two goals: (a) to understand needs and develop appropriate responses to task requirements, and (b) to configure individually and tailor to adopter needs.…”
Section: E-service Innovationmentioning
confidence: 99%
“…Firm's market and competition is also has a significant impact on the effectiveness of firm's market sensing capability (Kohli and Jaworski, 1990). A Firm that operates in turbulence markets is forced to make additional adjustments and adaptations on the process of information absorption than do other firms operate in stable markets (Kim, N., and Jae, H. P., 2007). Finally, regulatory environment has been recognized as a critical environmental factor influences the diffusion of innovation.…”
Section: Literature Reviewmentioning
confidence: 99%